Maintenance Agreements for the Elderly: Canada, 1900-1951 - Snell, James (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1992)
AbstractMaintenance agreements were a traditional mechanism by which the elderly gained economic security for themselves and ensured the continuing viability of the family economy. Over the later decades of the nineteenth century and the first half of the twentieth century in Canada, variations to this traditional process developed. The wage-labour opportunities available to young adults altered their dependence on family property, that itself was often changing incharacter. Reduced dependence loweredthe elderly parents' obligation to use the property to sustain the family over succeeding generations, even allowing the elderly to disperse or alienate the property. New forms of property could also be employed to somewhat altered purposes — the property no longer had to sustain an entire family culture and way of life, but simply to maintain its owners. Thus, an age-old custom was adapted by the elderly to meet their needs in circumstances of fundamental economic and social change.